Adopting and Implementing Collaborative Invitation, Exploration, Proposing-Explanation and Taking-action (CIEPT) Instructional Approach and Students’ Academic Performance in Chemistry - Ajayi, Victor Oluwatosin; Tanko, Christina Audu (Journal of Educational Technology and Instruction, 2023)
The study was on the adoption of the Collaborative Invitation, Exploration, Proposing-Explanation, and Taking action (CIEPT) instructional approach to design chemistry lesson plans and investigating if the implementation the of CIEPT instructional approach in chemistry classrooms could improve students’ academic performance. A pretest, posttest, control group, and quasi-experimental research design was adopted in this study. The instrument used for data collection was the Chemistry Academic Performance Test (CAPT). CAPT was adopted from the West African Examination Council (WAEC) past examination question papers of 2005-2022. Kuder-Richardson (KR-21) formula was used to test the internal consistency of CAPT which yielded a reliability value of 0.91. A sample of 152 students was purposively sampled from 4 schools out of 47 schools in the study area. Three research questions and three null hypotheses guided the study. The research questions were answered using Mean and Standard Deviation scores while the null hypotheses were tested at 0.05 level of significance using results from Analysis of Covariance (ANCOVA). The study revealed that there is a significant difference between the mean academic performance of students taught Chemistry using CIEPT and the discussion method of teaching [F1, 151=111.210, p<0.05]. It was found that no significant difference between the mean academic performance of male and female students taught Chemistry using the CIEPT approach [F1, 78 =.420, P>0.05]. It was recommended among others that since the CIEPT approach was found to be an effective approach for improving students’ academic performance irrespective of gender; Chemistry teacher’s trainee and serving teachers should be trained on how to adopt and use the CIEPT approach.